The Development of Online Training Packages on Practical Infographic Techniques to Enhance Infographic Design Ability for University Personnel - Thongsuk, Narathathai; Thepnuan, Naruemon (Mahachula Academic Journal, 2024)
The objectives of this research were to: (1) develop online training packages on practical infographic techniques to enhance infographic design ability for university personnel to have quality, (2) study design competence infographics on practice for university personnel, and 3) study personals’ satisfaction of university personnel towards the online training packages on practical infographic techniques to enhance infographic design ability for university personnel. The samples were 30 personnel in Mahachulalongkornrajavidyalaya University. They were selected by using a simple random purposive method by the supervisor selecting representatives of each department. The research instruments consisted of online training package, media and content quality, assessment form, design competence assessment form, and satisfaction assessment form. The statistics used in the research were mean and standard deviation. The results showed that (1) the online training packages had the quality of the media at a good level with the average score of 4.39, and the content quality at a good level with the average score of 4.33; (2) the university personnel had design ability at a good level; and (3) the satisfaction of university personnel towards the online training packages was at a high level with the average score of 4.43.